Amifostine does not prevent activation of TGF beta 1 but induces smad 7 activation in megakaryocytes irradiated in vivo - Segreto, HRC; Ferreira, A. T.; Kimura, E. T.; Franco, M.; Egami, M. I.; Silva, MRR; Segreto, R. A. (Wiley-Blackwell, 2002)
Experiments were undertaken to assess the role of amifostine in the activation of latent TGFbeta1 and in the smad proteins cascade (smad 2/3, smad4, smad7), focusing on megakaryocytes, in the bone marrow irradiated in vivo. Non-irradiated megakaryocytes were negative for active TGFbeta1. Immunopositivity to active TGFbeta1 was detected in megakaryocytes 10 days after irradiation in amifostine- treated and untreated marrows. Smad 2/3 and smad 4 were strongly positive in the nucleus of megakaryocytes 10 days after irradiation. At the same time, a predominant hypocellular bone marrow with foci of hematopoiesis was observed with few megakaryocytes. An increase in the number of reticulin fibers was also seen. In amifostine-treated marrows, smad 2/3 and smad4 were not detected in the nucleus but were positive in the cytoplasm of megakaryocytes 10 days after irradiation. Coincidentally, bone marrows were cellular with megakaryocytes. Smad7 immunoexpression was detected in the cytoplasm of megakaryocytes in the non-irradiated, amifostine-treated and in the irradiated, amifostine-treated marrows. Data indicate that amifostine does not prevent latent TGFbeta1 activation in irradiated megakaryocytes. While TGFbeta1 signal transduction occurs in megakaryocytes in untreated bone marrows, it is inhibited in megakaryocytes in amifostine-treated marrows due to the induction of smad 7 activation. This is the first report showing smad 7 activation by amifostine. Our results also suggest a role for TGFbeta1 as an inhibitor of megakaryocytes in vivo. (C) 2002 Wiley-Liss, Inc.
Keywords: bone marrow; amifostine; gamma rays; TGF beta; smad cascade